Mpox infection in animals: A systematic review and meta-analysis - Bonilla-Aldana, D. Katterine (2024)
Mpox is a zoonotic disease that became epidemic in multiple countries in 2022. There is a lack of published systematic reviews on natural animal infection due to Mpox. We performed a systematic literature review with meta-analysis to assess animal Mpox prevalence. We performed a random-effects model meta-analysis to calculate the pooled prevalence and 95% confidence interval (95%CI) for prevalence studies. After the screening, 15 reports were selected for full-text assessment and included in qualitative and quantitative analyses. Ten reports assessed Mpox infection by molecular or serological tests (n = 2680), yielding a pooled prevalence of 16.0% (95%CI: 3.0–29.0%) for non-human primates; 8.0% (95%CI: 4.0–12.0%) for rodents and 1.0% (95%CI: 0.0–3.0%) for shrews. Further studies in other animals are required to define the extent and importance of natural infection due to Mpox. These findings have implications for public human and animal health. OneHealth approach is critical for prevention and control.